Preventing bank offenses in Iran by considering of the United States and Switzerland - Babaei, Amirmohammad; Abu Mohammad Asgarkhani, Seyyed Baqer Mirabbasi,; Sadeghi, Mohammad (Opción, 2019)
In this article, our goal is to introduce models of crime prevention models and after the introduction of crimes we will analyze the legal system of Iran, with the United States and Switzerland via qualitative comparative analysis. The results of the study indicated that the US legal system was the most applied preventing bank crimes Primary prevention and non-contraception are used. Also, depending on the amount of economic or financial crime they also use criminal offenses. In conclusion, anyone identifying the source of bank assets detecting and seizing assets that it knows or knows about criminal activity has been convicted